OPTIMIZATION OF PROBLEM-SOLVING SKILLS THROUGH THE APPLICATION OF CREATIVE PROBLEM-SOLVING MODELS ASSISTED BY ACCOUNTING CARDS - Rizky Yuniar Sururi; Sri Sumaryati; Muhtar Muhtar (Universitas PGRI Madiun, 2022)
ABSTRACTAccording to the national education paradigm of the 21st century, the goal of accounting learning emphasizes the ownership of skills needed in the 21st century, including problem-solving skills. The Creative Problem Solving (CPS) learning model was chosen to improve learners' ability to solve a problem with structured steps so that learners will be accustomed to honing problem-solving skills. This is a classroom action research carried out in two cycles: planning, action, observation, and reflection. The research subjects were 33 students of class X Accounting 3 SMK N 3 Surakarta. The data collection techniques are tests, observations, interviews, and documentation. Techniques for testing the validity of data using source triangulation. The results showed an increase in problem-solving ability from the medium category in first cycle to the high category in second cycle.ABSTRAKTujuan pembelajaran akuntansi menurut paradigma pendidikan nasional abad 21 menekankan pada kepemilikan keterampilan yang dibutuhkan pada abad 21, diantaranya kemampuan memecahkan masalah. Model pembelajaran Creative Problem Solving (CPS) dipilih untuk meningkatkan kemampuan peserta didik dalam menyelesaikan suatu masalah dengan langkah-langkah yang terstruktur, sehingga peserta didik akan terbiasa untuk mengasah keterampilan pemecahan masalah. Penelitian ini merupakan penelitian tindakan kelas (PTK) yang dilaksanakan dua siklus dengan tiap siklus terdiri dari perencanaan, tindakan, observasi dan refleksi. Subjek penelitian adalah 33 peserta didik kelas X Akuntansi 3 SMK N 3 Surakarta. Teknik pengumpulan data yang digunakan adalah tes, observasi, wawancara dan dokumentasi. Teknik untuk menguji keabsahan data menggunakan triangulasi sumber. Hasil penelitian menunjukkan terdapat peningkatan kemampuan pemecahan masalah dari kategori sedang pada siklus pertama meningkat menjadi kategori tinggi pada siklus kedua.